2018
DOI: 10.1002/jcb.27854
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects and mechanism of curcumin on myocardial injury induced by coronary microembolization

Abstract: Objective Coronary microembolization (CME) is a common complication during the percutaneous coronary intervention (PCI). CME‐induced local myocardial inflammation and myocardial apoptosis are the primary causes of progressive cardiac dysfunction. Curcumin exerts a protective role in various cardiovascular diseases; however, its effects in CME are yet to be clarified. Therefore, the current study investigated the effects of curcumin on myocardial inflammatory responses, myocardial apoptosis, and cardiac dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…tween serum Trop & cardiac expression of caspase 3. This agreed with Yeh et al (2005)andLiu et al (2017) Liu et al (2019). found that Cur effectively reduced myocardial injury, inhibited myocardial apoptosis and improved cardiac functions.…”
supporting
confidence: 91%
“…tween serum Trop & cardiac expression of caspase 3. This agreed with Yeh et al (2005)andLiu et al (2017) Liu et al (2019). found that Cur effectively reduced myocardial injury, inhibited myocardial apoptosis and improved cardiac functions.…”
supporting
confidence: 91%
“…This is consistent with the belief that besides its role in innate immune responses, TLR4 serves as a proinflammatory agent in murine myocardial I/R injury. Also, studies have exhibited that the effect of TLR4- mediated inflammatory response in I/R injury was related to activation of NF- κ B and other proinflammatory cytokines including TNF- α and IL-1 β [39, 40]. RC and RG have been shown to effectively inhibit proinflammatory cytokine production because of their immunomodulatory effects [1921].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of myocardial inflammation and apoptosis can distinctly improve cardiac function and myocardial injury. 3,4 Moreover, studies by Liang et al 5 and Kong et al 6 demonstrated that myocardial apoptosis and inflammation can induce heart dysfunction and myocardial injury, after CME in rats. However, pretreatment with ligustrazine significantly reduced myocardial apoptosis and inflammation induced by CME, thus relieving myocardial injury and ameliorating cardiac contractile function by activating the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway.…”
Section: Introductionmentioning
confidence: 99%